A steady rise in incidence of pertussis since nineties in the Czech Republic - Fabiánová, K; Benes, C; Kríz, B (Epidemiologie, mikrobiologie, imunologie, 2010)
STUDY OBJECTIVE: The objective was to analyze the incidence and trends of pertussis in the Czech Republic, particularly by age groups. An important part of the analysis was the immunization coverage. MATERIALS AND METHODS: The incidence data were obtained from the following information sources: archives of the National Institute of Public Health for the period up to 1964, archives of the Institute of Health Information and Statistics for 1965-1981, Communicable Disease Information System for 1982-1992 and Communicable Disease Notification System EPIDAT for 1992-2008. The mortality data were obtained, apart from the aforementioned sources, also from the literature. The case definition was based on that provided by the Bulletin of the Ministry of Health and the EC Directive. Cases were notified in accordance with the guidelines of the respective information systems and the principles of pertussis surveillance laid down by the regulations. An epidemiological investigation form was filled in for each case of pertussis, indicating the type of laboratory analysis. The methods used for laboratory diagnosis of pertussis were culture, serology and a PCR assay. RESULTS: An upward trend in notified cases of pertussis has been observed since the 1990s. The highest annual number of cases (767) in the last 42 years was notified in 2008 (7.3/100,000 population). In 1988-2008, most (93.1%) cases were notified in patients aged 0-19 years. During this period the peak moved from the youngest and preschool age groups toward younger and older school age children (the highest age-specific incidence of pertussis, i.e., 79.8/100,000, was observed in 10-14-year-olds. In 2008, a 3.4 fold rise in pertussis cases was observed in 15-19-year-olds as compared with the rates in the last six years. More cases were also notified in the age groups of potential parents and grandparents. In the 0- year-old children, the incidence of pertussis was decreasing since the 1950s (3804.9/100,000 in 1956) to remain under 10.0/100,000 between 1974 and 1999. It showed a continuing upward trend from 3.8/100,000 in 1987 to 26.7/100,000 in 2008, even with three deaths notified, after 35 years, in 2005, 2007 and 2009. CONCLUSION: Despite the high immunization coverage with pertussis vaccine (>97%), the pertussis incidence is rising in the Czech Republic. An upward trend in pertussis cases has been observed since 1993, peaking in 2008. More than 75 % of pertussis cases were notified in patients who had been vaccinated with 5 doses of pertussis vaccine before infection. During the period 1988-2008, the highest age-specific incidence, i.e., 79.8/100,000, was observed in 10-14-year-olds. After 35 years, three deaths from pertussis were notified in 2005, 2007 and 2009. All three fatal cases occurred in unvaccinated children under one year of age. The focus needs to be on active surveillance of pertussis and quality improvement of all its parts.
Keywords: novorozenec; Infant, Newborn; vakcinace; Infant; Humans; kojenec; dítě; Vaccination; Child; mladý dospělý; lidé; pertuse; předškolní dítě; Adolescent; incidence; Incidence; Czech Republic; Young Adult; Whooping Cough; Česká republika; Child, Preschool; mladiství